Recent Advances in Electrochemical Cascade Cyclization Reactions - Zhang, Cai; Chen, Demao; Wan, Jie-Ping; Liu, Yunyun (Synthesis, 2023)
This review highlights recent progress in electrochemical cascade cyclization reactions for the synthesis of carbon rings and heterocycles, such as pyridines, quinolines, phenanthridines, cinnolines, 1,4-dihydroquinolines, oxindoles, imidazo[1,5-α]pyridines, imidazoles, etc. The works included herein are introduced in two major sections of heterocycle construction and carbocycle construction reactions, covering the works reported from 2012 to 2022.1 Introduction2 Electrochemical Cascade Cyclization for the Synthesis of Heterocycles2.1 Synthesis of Pyridines, Quinolines, Phenanthridines, and Cinnolines2.2 Synthesis of 1,4-Dihydroquinolines, Hexacyclic Sulfonamides, and Thiazines2.3 Synthesis of Hydroisoquinolinones and Hydroquinolinones2.4 Synthesis of Quinazolin-4(3H)-ones2.5 Synthesis of 4H-3,1-Benzoxazines2.6 Synthesis of Oxindoles2.7 Synthesis of Indolines and Indoles2.8 Synthesis of Imidazo[1,5-α]pyridines and Imidazoles2.9 Synthesis of Imidazolones, Imidazolidinones, Oxazolones, and Oxazolidinones2.10 Synthesis of Benzoxazoles, Oxazolines, and Isoxazolines2.11 Synthesis of Furans and Dihydrofurans2.12 Synthesis of Indolizines, Pyrazoles, and Triazolium Inner Salts2.13 Synthesis of Sulfonated Benzothiophenes, Thiazoles, Dihydrothiazoles, and 1,3,4-Thiadiazoles2.14 Synthesis of Lactones3 Electrochemical Cascade Cyclization for the Construction of Carbocycles3.1 Synthesis of Carbon Polycycles and Spiroindenes3.2 Synthesis of Difluoroacyl (Hetero)arenes and Sulfonated Indenones4 Conclusion
Keywords: electrochemical; cascade cyclization; heterocycle; carbocycle; green synthesis